Isolation of Radial Glia-Like Neural Stem Cells from Fetal and Adult Mouse Forebrain via Selective Adhesion to a Novel Adhesive Peptide-Conjugate - Markó, Károly (Public Library of Science, 2011)
Preferential adhesion of neural stem cells to surfaces covered with a novel synthetic adhesive polypeptide (AK-cyclo[RGDfC]) provided a unique, rapid procedure for isolating radial glia-like cells from both fetal and adult rodent brain. Radial glia-like (RGl) neural stem/progenitor cells grew readily on the peptide-covered surfaces under serum-free culture conditions in the presence of EGF as the only growth factor supplement. Proliferating cells derived either from fetal (E 14.5) forebrain or from different regions of the adult brain maintained several radial glia-specific features including nestin, RC2 immunoreactivity and Pax6, Sox2, Blbp, Glast gene expression. Proliferating RGl cells were obtained also from non-neurogenic zones including the parenchyma of the adult cerebral cortex and dorsal midbrain. Continuous proliferation allowed isolating one-cell derived clones of radial glia-like cells. All clones generated neurons, astrocytes and oligodendrocytes under appropriate inducing conditions. Electrophysiological characterization indicated that passive conductance with large delayed rectifying potassium current might be a uniform feature of non-induced radial glia-like cells. Upon induction, all clones gave rise to GABAergic neurons. Significant differences were found, however, among the clones in the generation of glutamatergic and cathecolamine-synthesizing neurons and in the production of oligodendrocytes.